Mechanical characterisation of pneumatically-spliced carbon fibre yarns as reinforcements for polymer composites. (January 2022) - Davidson, James R.; Quinn, James A.; Rothmann, Claudia; Bajpai, Ankur; Robert, Colin; Ó Brádaigh, Conchúr M.; McCarthy, Edward D.
Graphical abstract: Highlights: Spliced tows recovered up to 46% of loads and 64% linear stiffness of pristine tows. Number of released air blasts correlates asymptotically to stiffness and strength. Spliced reinforced composites recovered 69.3–70.4% Modulus and 43.0–44.0% strength. Results indicate that pneumatic splicing could be valuable for composite recycling. Abstract: An investigation into the mechanical response of pneumatically-spliced carbon fibre yarns as a potential reinforcing material for polymer composites is presented. High strength mechanical connections between carbon fibre yarns are produced by joining short discontinuous tows into longer lengths via fibre entanglement. The effect of altering the number of high-pressure air pulses fired by a commercially available (Airbond 701H) splicing machine, to form the tow-tow connection, on load bearing capacity and linear stiffness is first evaluated on splices between virgin T700SC-24K-50C carbon fibre tows. The best performing spliced configuration is subsequently utilised in reinforcing unidirectional epoxy laminates, which are mechanically characterised, and their properties compared to those of various continuous fibre and chopped strand mat panels. Results presented in this study demonstrate that pneumatic splicing provides a high strength and sustainable solution for reinforcing polymers with discontinuous (approx. > 50 mm in length) virgin, off-cut or waste carbon fibre yarns. It is speculated that with further research, quasi-continuous yarns remanufactured by splicing waste fibres could provide a novel material for weaving, braiding, non-crimp fabrics, or use in 3D printing applications.